The Place and Role of Physics in Scientific and Technical Development - Abdiyeva Nilufar Azod's daughter (Scientific Trends, 2024)
This article is about the importance of physics in the development of society and science and technology and its interrelationship with other disciplines. Provides brief information about the methodology of teaching physics and the importance of using innovative technologies.
Keywords: Revolution, polytechnic education, virtual laboratories, mechanics, quantum physics, nanotechnology, microscopes, robotics.